(untitled) (Fiep Bulletin - online, 2014)
New concept of world, ways differentiated in relations personal and with de nature, implies in change deep and rooted in new values, new paradigms. Worry with the quality of the way where we live in them leads to reflect if we are commitment and made use to stop a battle in future the better defense of condition of life. To extend it discussion the search of an ambient conscience we need to elucidate some subjects as: vision of altogether, empowerment, quality of life, environmental justice. This study has as objective to argue the questions environmental of inside where to worry with the environment this directly related with the quality of life of the person. The Environment Educacion serves of for subsidy to Fisycal Educacion, that considers the human being as an alive bory, but not explored bory. It is way of restoration of the equilibrium of the humam being with the nature and consists mainly in a respectful attitude stops with the environment.